2005
DOI: 10.1016/j.jdermsci.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

DNFB activates MAPKs and upregulates CD40 in skin-derived dendritic cells

Abstract: Taken together, these results indicate that the strong sensitizer DNFB activates ERK1/2 and p38 MAPK signaling pathways, and upregulates CD40 protein levels. However, MAPKs do not play a major role in the induction of CD40, one of the phenotypic markers of DC maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…Accordingly, it was previously demonstrated by us and other authors that LPS and skin sensitizers activate MAPK signalling pathways in DC [4,31,37,40,57]. In addition, MAPK are involved in the induction of Nrf2/ARE-dependent gene expression [66].…”
Section: Introductionmentioning
confidence: 91%
“…Accordingly, it was previously demonstrated by us and other authors that LPS and skin sensitizers activate MAPK signalling pathways in DC [4,31,37,40,57]. In addition, MAPK are involved in the induction of Nrf2/ARE-dependent gene expression [66].…”
Section: Introductionmentioning
confidence: 91%
“…In contrast to other DC lines used for studying skin sensitisation hazards, FSDC have the advantage of being cultured in the absence of exogenous recombinant growth factors. We observed that the sensitisers, 2,4-dinitrofluorobenzene (DNFB) and nickel, increased the expression of the membrane-associated proteins CD40 and interleukin (IL) 12 receptor, whereas the non/very weak skin sensitiser 2,4-dichloronitrobenzene (DCNB) did not affect the expression of either protein (Vital et al, 2004;Matos et al, 2005a). Recently, we also found that the CXCR4 chemokine receptor is selectively modulated by skin sensitisers (and not by irritants) in FSDC (Neves et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, expressions of major histocompatibility (MHC) class II molecules and costimulatory molecules, such as, CD40, CD54, CD83, and CD86 are upregulated in DCs exposed to contact sensitizers (5-7). Furthermore, contact sensitizers reportedly activate p38 MAP kinase and ERK1/2 in the pathway leading to CD40 upregulation, and these activations are dependent on ROS (reactive oxygen species) (8,9).…”
Section: Introductionmentioning
confidence: 99%